2015
DOI: 10.1371/journal.pone.0127551
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative Stress Induced by Zearalenone in Porcine Granulosa Cells and Its Rescue by Curcumin In Vitro

Abstract: Oxidative stress (OS), as a signal of aberrant intracellular mechanisms, plays key roles in maintaining homeostasis for organisms. The occurrence of OS due to the disorder of normal cellular redox balance indicates the overproduction of reactive oxygen species (ROS) and/or deficiency of antioxidants. Once the balance is broken down, repression of oxidative stress is one of the most effective ways to alleviate it. Ongoing studies provide remarkable evidence that oxidative stress is involved in reproductive toxi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
62
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 88 publications
(67 citation statements)
references
References 55 publications
5
62
0
Order By: Relevance
“…PCR reactions were initiated at 95°C for 10 min, followed by denaturing at 95°C for 10 sec, annealing at 60°C for 30 sec and 72°C for 10 sec. After 40 cycles, there was a cooling step at 4°C [24]. Housekeeping gene GAPDH was used to normalize the gene expression level.…”
Section: Calculation Of Index Of Ovary/body Weightmentioning
confidence: 99%
“…PCR reactions were initiated at 95°C for 10 min, followed by denaturing at 95°C for 10 sec, annealing at 60°C for 30 sec and 72°C for 10 sec. After 40 cycles, there was a cooling step at 4°C [24]. Housekeeping gene GAPDH was used to normalize the gene expression level.…”
Section: Calculation Of Index Of Ovary/body Weightmentioning
confidence: 99%
“…The oxidative stress is often caused by redox homeostasis breakdown between ROS particularly free radicals and enzymatic or non-enzymatic antioxidants [ 9 ]. The homeostatic imbalance due to overproduction of reactive oxygen species (ROS) and/or a deficiency in antioxidants, particularly under abiotic stress generally induces and exacerbates oxidative stress [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Qin et al () have reported that curcumin is effective at reducing a dysregulation in the cellular redox balance. Feng, Tao, Yan, Chen, and Qin () have also reported that curcumin inhibits apoptosis and protects against mitochondrial injury and inhibits the intrinsic apoptotic pathway.…”
Section: Discussionmentioning
confidence: 99%